Sherlock Holmes essentials. Vol. 2 [compact disc] - Doyle, Arthur Conan, 1859-1930 (Audio Go/BBC Audiobooks America, 2010)
Presents six mystery stories about the adventures of the intrepid detective Sherlock Holmes and his chronicler Dr. Watson.